1989
DOI: 10.1177/154193128903300520
|View full text |Cite
|
Sign up to set email alerts
|

A Benchmark Comparison of Mouse and Touch Interface Techniques for an Intelligent Workstation Windowing Environment

Abstract: This study presents evidence that a prototype touch interface technology emulating basic interaction techniques of a mouse pointing device is comparable in overall usability to a conventional mousc? for a direct manipulation, graphical windowing software environment. The touch technology prototype involves using either a stylus or finger, with an overlay sensitive to changes in capacitance. Users practiced each technique (mouse,' stylus, finger, keyboard with no mouse), in the context of carrying out office-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…A more typical performance-preference dissociation was illustrated in a study by Mack and Lang (1989), who found that although subjects made significantly more precision pointing errors using a stylus and a mouse, they preferred these two input methods over the keyboard-command input method. Bailey (1991) performed a study in which 30 subjects completed a series of tasks in a software application that had either a consistent interface, a moderately consistent interface, or an inconsistent interface.…”
Section: Computer-based Systemsmentioning
confidence: 99%
“…A more typical performance-preference dissociation was illustrated in a study by Mack and Lang (1989), who found that although subjects made significantly more precision pointing errors using a stylus and a mouse, they preferred these two input methods over the keyboard-command input method. Bailey (1991) performed a study in which 30 subjects completed a series of tasks in a software application that had either a consistent interface, a moderately consistent interface, or an inconsistent interface.…”
Section: Computer-based Systemsmentioning
confidence: 99%
“…Such improvements support direct manipulation techniques like dragging, which are prominent in state-ofthe-art graphical user interfaces. A recent study by Mack and Lang (1989; see also Potter, R., Berman, M. and Shneiderman, 1989) found that users could complete realistic office tasks as quickly using the stylus as they could with a mouse, using commercially available applications running under a graphical windowing environment (Microsoft Windows). In this study, touch interactions emulated basic mouse interactions like clicking, double-clicking, and dragging.…”
Section: Introductionmentioning
confidence: 97%
“…• Finger-operated touch screen g p -Best in speed and worst in accuracy (Albert, 1982) • Stylus(Pen)-operated touch screen -Comparable to a mouse on both speed and accuracy measures (Mack & Lang, 1989) (used with permission of Smart Technology) …”
Section: Experimental Results Experimental Resultsmentioning
confidence: 99%